(untitled) (Web of Teachers: Inderscience Research, 2025)
This article provides an in-depth examination of educational robotics as a pedagogically significant tool for shaping engineering thinking in school-aged learners. It expands upon key instructional approaches—project-based learning, laboratory–practical exercises, and competition-oriented models—while offering a detailed analysis of robotics platforms commonly integrated into modern educational environments. Particular attention is devoted to the interdisciplinary nature of robotics education, which simultaneously draws on mathematics, physics, computer science, engineering graphics, and technological design. The article develops an extended conceptual framework describing how robotics fosters systemic reasoning, algorithmic literacy, creativity, technical reflection, and problem-solving skills. Several examples of educational robotics projects are presented, categorized by complexity and instructional value. The expanded findings reinforce the conclusion that sustained and systematic use of robotics not only enhances motivation and digital literacy but also cultivates essential 21st-century competencies required in contemporary engineering and technological professions.